PERAN KEBIJAKAN DAN TEKNOLOGI DIGITAL DALAM MENUJU SUNGAI BERKELANJUTAN DIKOTA BANJARMASIN - Anjani; Norhalidah; Panggih Prabowo Rona Saputra; Mutmainnah; Sidderatul Akbar (stiatabalong.ac.id, 2026)
Rivers are vital assets of Banjarmasin City, currently facing environmental degradation due to urbanization and low community understanding. This study aims to analyze the role of policy and digital technology in achieving sustainable river management in Banjarmasin. The research method employed is qualitative with a descriptive approach. Data were collected through observation, documentation, and interviews with key informants, including the Banjarmasin City Public Works and Spatial Planning Department (PUPR), riverbank communities, and related organizations. The data analysis technique applied is thematic analysis. The results show that although Regional Regulation No. 15 of 2016 provides a strong legal foundation, low community literacy regarding river regulations remains a major obstacle to policy implementation. Optimizing digital technology through social media and monitoring systems serves as a strategic solution to enhance education, information transparency, and collective participation in maintaining the river ecosystem. This study concludes that river sustainability in Banjarmasin heavily depends on the synergy between firm government policies and the utilization of digital instruments to build community engagement as active subjects in management. The practical implication of this research emphasizes the importance of digital education to increase policy effectiveness, while theoretically, it strengthens the argument that digital governance is a vital instrument in managing Common Pool Resources in urban environments